Design, implementation and analysis of a spreadsheet for formulation of parenteral nutrition formulas in neonates with pharmaceutical support (Horizontes de Enfermería, 2018)
A spreadsheet for neonatal parenteral nutrition formulation was designed in this study, based on the requirements suggested by the international literature, and compared with the data obtained from the manual method formulation and an online calculator. It is worth to point that neither the manual method or the online calculator, had considering the characteristics of each brand of medicines used in parenteral nutrition. This spreadsheet allowed the pharmacist to access both patient data and formulation relevant data that were on the same spreadsheet. A retrospective study of 40 neonatal parenteral nutrition formulations was conducted at the Luis Gabriel Davila Hospital between the months of January and November 2014, including only patients who received seven or more days of parenteral nutrition. It was compared with the results of the three methods: manual, online calculator and developed spreadsheet. The comparison of the results was done with a completely random block design with an analysis of variance and a 5% Duncan test. It was found that the manual method tends to overestimate the amount of lipids and vitamins of the B complex, while it tends to underestimate the quantities of the rest of the variables analyzed. In addition, there is a clear tendency for the online calculator to overestimate the volumes of all components of parenteral nutrition and also the values "‹"‹of the GIR and osmolarity. The variables that no hade significant differences between the three methods were: total kilocalories, amino acids volume and ratio of non-protein kilocalories / g of nitrogen. The incorporation of knowledge of the pharmacist helped to improve the neonatal parenteral formulation avoiding over or sub-dosing of its components.
Keywords: Parenteral nutrition; manual method; online calculator